Elbow Medial Compartment Disease in a Dog - Treatment with Proximal Abducting Ulnar (PAUL) - Pacheco, Larissa Teixeira; Augusto Lopes Muzzi, Leonardo; Natsuki Honda, Cláudia; da Silva Paulino, Jussani; Munhoz Garcia Perez Neto, Daniel; Orlando Barbosa Momesso, Eric (Acta Scientiae Veterinariae, 2025)
Background: Medial compartment disease (MCD) is characterized by the degeneration of the articular cartilage in the medial compartment of the elbow joint. Various surgical interventions are employed to manage this condition, with the proximal abducting at altering the load distribution across the elbow joint. This procedure is intended to offload the medial compartment, alleviate pain, and decelerate the progression of osteoarthritis. Despite its theoretical benefits, the long-term outcomes, efficacy, and potential complications associated with PAUL osteotomy remain incompletely understood. The present report describes the application of PAUL osteotomy in the surgical treatment of a dog with MCD, utilizing a specialized bone plate. Case: A 2-year-old male Chow Chow dog, weighing 32 kg, was referred to the University Veterinary Hospital with a history of chronic thoracic limb lameness. Upon physical examination, moderate lameness was noted in both forelimbs, accompanied by shortening of the stride, a narrowed base of support, slight pronation of the forearms, and mild adduction of the left elbow. Radiographic evaluation of both forelimbs revealed advanced osteoarthritic changes, with similar alterations observed in both elbows, supporting the diagnosis of medial compartment disease. Initial conservative management, including physical therapy, was instituted; however, the patient exhibited intolerance to the prescribed regimen and failed to show significant improvement over a 6-month follow-up period. Consequently, the decision was made to proceed with PAUL osteotomy. Preoperative radiographs revealed a mechanical medial elbow angle (mMEA) of 84.8º. The surgical approach involved a caudo-lateral incision over the left ulna, with osteotomy performed distally at the midshaft of the ulna. A bone plate was applied, with a 3 mm step at the proximal fragment. Postoperatively, partial weight-bearing was observed within 24 h, with moderate lameness. Clinically, there was notable improvement in weight-bearing capacity and a reduction in both elbow adduction and forearm pronation by 30 days post-surgery. A satisfactory clinical outcome was achieved by 120 days postoperatively. Follow-up radiographs at 90 days demonstrated an improved mMEA of 88.5º. Radiographic healing of the osteotomy site was evident at 180 days, and no complications were observed through 280 days post-surgery. During the 4-year follow-up, radiographic evaluation revealed complete consolidation of the osteotomy and marked improvement in the articular surface of the operated elbow. Notably, there was reduced osteophyte formation in the region of the medial epicondyle, and no progression of osteoarthritis was detected, indicating a favorable long-term outcome. The dog demonstrated excellent weight-bearing on the affected limb, with no signs of lameness. Discussion: The results of this case suggest that PAUL osteotomy, performed without concomitant elbow arthrotomy, is an effective surgical treatment for MCD, leading to significant improvements in both clinical outcomes and quality of life. Notable improvements were observed in the lameness score, reduction of joint pain, and an increase in the range of motion. The owner reported high satisfaction with the procedure, and radiographic evidence demonstrated no progression of osteoarthritis during the 4-year evaluation period. Importantly, distal placement of the osteotomy and the implant did not adversely affect the clinical or radiographic outcomes. These findings support the potential of PAUL osteotomy as a viable long-term solution for managing MCD in dogs, particularly in cases unresponsive to conservative treatments. Keywords: elbow dysplasia, osteoarthritis, mechanical medial elbow angle. Título: Síndrome do compartimento medial do cotovelo em cão - tratamento com osteotomia abdutora proximal da ulna (osteotomia PAUL) Descritores: displasia de cotovelo, osteoartrose, ângulo mecânico medial do cotovelo.